Oxychalcogenide Perovskite Solar Cells: A Multiscale Design Approach. Issue 4 (2nd April 2020) - Park, Heesoo; Baloch, Ahmer A. B.; Bentria, El Tayeb; Rashkeev, Sergey N.; Alharbi, Fahhad H.; El-Mellouhi, Fedwa
Abstract : A multiscale approach illustrates the high power conversion efficiency (PCE) of a solar cells with oxychalcogenide perovskites. Based on the atomistic‐scale properties, full device simulation maximizes the PCE by optimizing multiple properties in a device. This approach guides identification of potential oxychalcogenide perovskite solar cells. More details can be found in article number 1900766 by Fedwa El‐Mellouhi and co‐workers.